Management decision making & action in behavioral situations : an introduction to behavioral sciences for sciences for business managers - Mockler, Robert J. (Austin ; Texas : Austin press, 1973)
Two lonely cowboys have a mysterious visitor on Christmas Eve.
Keywords: Santa Claus -- Fiction; Cowboys -- Fiction; Christmas -- Fiction; Stories in rhyme; Texas -- Fiction